Pitfalls of Forward-Looking Monetary Policy - Woodford, Michael (American Economic Review, 2000)
From page 100 – "A distinctive feature of the procedures recently adopted by inflation-targeting central banks is their forward-looking character. Forecasts of the economy’s future evolution conditional upon alternative policies play a central role in the banks’ deliberations, to an extent that the procedures adopted are sometimes characterized as “forecast targeting.” This emphasis upon the future consequences of policy is unsurprising in an approach that tries to maintain as transparent as possible a relation between the banks’ decisions and the ultimate goals of monetary policy; after all, current decisions can still affect the future, but not the past. Nonetheless, common descriptions of how inflation targeting is or should be practiced go too far, in proposing purely forward-looking procedures. I shall argue instead that an optimal framework for the conduct of monetary policy must generally be history-dependent in ways precluded by these simple proposals. This follows from a general feature of the optimal control of a forward-looking system, which is to say, one in which the private sector’s expectations about future policy are an important determinant of the effects of monetary policy."